Competitive advantages through IT-enabled Supply Chain Management (SCM) context - Tarofder, Arun Kumar; Jawabri, Adnan; Haque, A. K. M. Ahasanul; Azam, S. M. Ferdous; Sherief, Sultan Rehman (Czestochowa University of Technology, 2019)
Abstract: The primary aim of this study is to investigate the effect of IT-enabled supply chain on the operational and strategic benefits, which eventually ensures firms competitive advantages. A conceptual model was developed based onthe theory of competitive advantage suggested by Porters and also extensive empirical study. The questionnaire was developed based on several steps and items were adopted from several prior studies. Stratified random sampling was employed to collect data from 203 respondents. Based on structural equation modelling, IT-enabled SCM is able to offer a wide range of operational benefits, instead of strategic. Results were antagonized several prior studies and confirmed that competitive advantages greatly depend on operational benefits rather than strategic. This is study is one of the very few empirical investigations that investigate the benefits of IT from two different perspectives and their effects of competitive advantages. Findings of this study will help managers to understand the importance of IT-enabled SCM in their organizations.